2020
DOI: 10.31557/apjcc.2020.5.3.133-138
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Nursing Students Towards Smokeless Tobacco and Areca Nut Control in Central Province of Sri Lanka

Abstract: Background: Use of smokeless tobacco (SLT) and areca nut (AN) is widespread in Sri Lanka. Several workshops to train healthcare workers on SLT/ AN cessation programmes (SLT/AN-CP) were carried out. Objective of the study was to evaluate the enhancement of knowledge and attitudes related to SLT/AN-CP among nursing students following a workshop. Methods: A cross sectional study was conducted with the use of two questionnaires. A total of 212 nursing students were assessed and the study group included 184 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…This prevalence of tobacco use is relatively low compared with results from other studies conducted amongst school teachers in Odisha (smoked tobacco -28%; smokeless tobacco 68%) and Bihar (smoked tobacco -43%; smokeless tobacco 57%) (Sinha and Gupta., 2004;Sinha et al, 2004). While, in a recent survey conducted in Sri Lanka among 212 nursing students showed that 73.1% knew that "areca nut is an addictive substance", 76% respondents in our study stated that tobacco is addictive (Hettiarachchi, Jayasooriya, Amarasinghe, et al, 2020).…”
Section: Discussioncontrasting
confidence: 75%
“…This prevalence of tobacco use is relatively low compared with results from other studies conducted amongst school teachers in Odisha (smoked tobacco -28%; smokeless tobacco 68%) and Bihar (smoked tobacco -43%; smokeless tobacco 57%) (Sinha and Gupta., 2004;Sinha et al, 2004). While, in a recent survey conducted in Sri Lanka among 212 nursing students showed that 73.1% knew that "areca nut is an addictive substance", 76% respondents in our study stated that tobacco is addictive (Hettiarachchi, Jayasooriya, Amarasinghe, et al, 2020).…”
Section: Discussioncontrasting
confidence: 75%
“…It means that the tobacco control policy in a school within a regency is highly depend on each local government whether they are already set this regulation or not. Thus, established evidences suggested that the SFZ campaign and strategies are necessary to all parties not only to the local government, but also to mass community (Veruswati et al, 2020) including students (Hettiarachchi et al, 2020) should be taken into account in reducing the youth smokers as the designated mission of all countries with high burden of tobacco consumption.…”
Section: Discussionmentioning
confidence: 99%
“…6 And in Sri Lanka, several workshops held among student nurses resulted in an enhanced knowledge and attitude towards the use of ST as well as to areca nut (a stimulant from areca palm). 8 While assessing health knowledge and attitudes regarding ST consumption and its health effects among married women in a rural Bangladesh, it appeared that half of the participants believed that ST consumption had a positive impact on their health, and they attached to it some medicinal properties such as it being able to resolve stomach pains. However, on the other hand in the same area, some participants intended to quit the use of these products.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In addition, the use of tobacco (smoking or smokeless) is associated with increased risk of other chronic and terminal diseases such as periodontal diseases, oral and pharyngeal cancers, erectile dysfunction, pregnancy-related issues such as stillbirth and low birthweight neonates, heart diseases, and more. 8 Regarding the users’ demographics for this practice, it appeared that the majority were less than 30 years old, according to a Korean study. 9 In a Bangladeshi study, current consumption of ST products among married women was associated with age (over 25 years), low education level, occupation and religion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation